(untitled) (Discourse of Law and Administration, 2022)
In proceedings under civil law, grounds for a cassation complaint may include a breach of procedural provisions, should such infringement have considerable impact on the outcome of the case. The specific nature of grounds for invalidity means that the breach of procedure bears significant effect on the outcome of the case a priori. Finding grounds for invalidity is not tantamount to finding to the effect of invalidity of proceedings. The declaration of invalidity is a procedural qualification, i.e. an inference based on appraisal, whereby grounds for invalidity are recognised as the basis for qualification; qualification may result in annulment, i.e. unconditional exclusion of the option to adjudicate by rejecting the claim, or conditional exclusion by discontinuing proceedings to the extent they had been affected by invalidity and referring the case for re-examination. During cassation proceedings and taking grounds for invalidity identified in appeal proceedings into account, the Supreme Court renders such proceedings invalid. Conversely, identifying reasons for rendering proceedings invalid found in first-instance proceedings yet unnoticed at the time, affords the possibility of single-stage (grounds for invalidity resulting in annulment) or double-stage (grounds for invalidity resulting in abolition) examination, and – consequently – rendering proceedings invalid.